2018
DOI: 10.24297/jaa.v8i1.7525
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Purslane Plant Using Cooking and Pickling Processes for Reducing Oxalate Conten

Abstract: Purslane (Portulaca oleracea) is an edible plant rich in beneficial nutrients. Chemical composition, mineral composition, fatty acids, total phenolic compounds and radical scavenging activity of purslane were determined. In addition, oxalate content of purslane was analyzed after cooking at three temperatures (60, 80 and 100 °C) for different durations (5, 10, 15 and 20 minute), and pickling for various durations (3, 6 and 9 days). Fatty acid analysis, sensory evaluation and quality characteristics of biscuits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Blanching has been shown to be effective in removing oxalates from vegetables [49] In a study of the edible halophyte Portulaca oleracea, boiling the leaves, stems, or flowe buds for five minutes reduced the total oxalate in the tissues by, on average, 27% [50]. In a similar study on P. oleracea, Badawy et al [51] showed that as the heating time and tem perature were increased, soluble oxalate levels in the tissue decreased concomitantly Blanching the leaves of the halophyte Tetragonia expansia reduced the total oxalate by 25% when they were placed into boiling water for two minutes [52]. Pickling leaves in vinega has also been successfully used to reduce the oxalate content, although to a lesser exten than blanching [50,51].…”
Section: Processing As a Means To Reduce Oxalatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blanching has been shown to be effective in removing oxalates from vegetables [49] In a study of the edible halophyte Portulaca oleracea, boiling the leaves, stems, or flowe buds for five minutes reduced the total oxalate in the tissues by, on average, 27% [50]. In a similar study on P. oleracea, Badawy et al [51] showed that as the heating time and tem perature were increased, soluble oxalate levels in the tissue decreased concomitantly Blanching the leaves of the halophyte Tetragonia expansia reduced the total oxalate by 25% when they were placed into boiling water for two minutes [52]. Pickling leaves in vinega has also been successfully used to reduce the oxalate content, although to a lesser exten than blanching [50,51].…”
Section: Processing As a Means To Reduce Oxalatesmentioning
confidence: 99%
“…Blanching the leaves of the halophyte Tetragonia expansia reduced the total oxalate by 25% when they were placed into boiling water for two minutes [52]. Pickling leaves in vinegar has also been successfully used to reduce the oxalate content, although to a lesser extent than blanching [50,51]. While blanching is an option for the removal of oxalates from leaves, it causes wilting due to breakdown of the tissue, and it is therefore not recommended when crisp salad leaves are the desired product.…”
Section: Processing As a Means To Reduce Oxalatesmentioning
confidence: 99%
“…Purslane is a common, herbaceous succulent annual plant. It is distributed extensively in temperate and tropical regions worldwide (Badawy et al, 2018 andPetroplous et al, 2019). In Egypt it's commonly known as "Rejlah" (El-Gindy, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In current years, it has been re-evaluated as a potential "New Crop" for its positive properties which distinguish as one of the best vegetable sources of omega-3 fatty acids (linolenic acid) and for its great crude protein and water-soluble polysaccharide contents. (Badawy et al, 2018 andPetroplous et al, 2019). It has been informed to possess various pharmacological activities; it has been used throughout history for several different medicinal purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation